Polyarylene sulfide resin composition and composite made thereof

A polyarylene sulfide resin composition with specific ethylene polymer and glass fiber ratios addresses warpage and bonding issues, providing excellent properties for electronic and automobile components.

JP7615540B2Active Publication Date: 2025-01-17TOSOH CORP
View PDF 21 Cites 0 Cited by

Patent Information

Application Number
JP2020070938
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-04-10
Publication Date
2025-01-17
Estimated Expiration
2040-04-10

AI Technical Summary

Technical Problem

Existing polyarylene sulfide resin compositions face challenges in achieving low warpage, good bonding properties with metals, low dielectric constant, and low dielectric loss tangent, particularly in applications requiring complex shapes and smaller sizes such as mobile device housings and automobile electrical components.

Method used

A polyarylene sulfide resin composition comprising 30 to 70% polyarylene sulfide, 3 to 20% ethylene polymer, and 30 to 60% glass fiber with specific aspect ratios and dielectric constants, along with a mold release agent, to enhance bonding, reduce warpage, and improve impact resistance.

Benefits of technology

The composition exhibits excellent radio wave transparency, minimal warpage, and superior bonding with metals, making it suitable for electronic and electrical components like mobile device housings and automobile parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615540000001
    Figure 0007615540000001
  • Figure 0007615540000002
    Figure 0007615540000002
Patent Text Reader

Abstract

To provide a polyarylene sulfide resin composition which has: a small amount of warpage when used as a member; an excellent radio wave permeability from a megahertz band to a gigahertz band owing to having a low dielectric constant and a low dielectric loss tangent; and excellent impact resistance, and to provide a composite comprising the same.SOLUTION: There is provided a polyarylene sulfide resin composition comprising: 30 to 70 wt.% of a polyarylene sulfide (A); 3 to 20 wt.% of an ethylenic polymer (B); and 30 to 60 wt.% of glass fibers (C) having a dielectric constant of 5.5 or less at 2 GHz and a fiber cross- sectional aspect ratio of 2 to 4. There is also provided a metal member-polyarylene sulfide resin member composite comprising the same.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyarylene sulfide resin composition which has a low dielectric constant and a low dielectric tangent and therefore excellent radio wave transmittance in the megahertz to gigahertz bands, has a small amount of warping when integrated with a metal member, has excellent bonding properties with metal members and also has excellent impact resistance, and to a composite in which a polyarylene sulfide resin composition member is integrated with a metal member; and more specifically, the present invention relates to a polyarylene sulfide resin composition which is particularly useful for electric and electronic parts such as housings for mobile terminal devices such as mobile personal computers, tablets, and mobile phones, and a composite made of the same. [Background technology]

[0002] Polyarylene sulfides (hereinafter sometimes abbreviated as PAS), such as poly(p-phenylene sulfide) (hereinafter sometimes abbreviated as PPS), have excellent mechanical properties, thermal properties, electrical properties, and chemical resistance, and are widely used in many electrical and electronic equipment components, automotive equipment components, and other office automation equipment components.

[0003] PAS can greatly improve mechanical strength, heat resistance, rigidity, etc., by blending fibrous inorganic fillers such as glass fiber, and granular inorganic fillers such as calcium carbonate and talc. However, blending fibrous fillers causes warping in molded products, limiting their use in electronic and electrical component applications such as the housings of mobile terminal devices such as mobile PCs, tablets, and mobile phones, and electrical component applications such as automotive electrical components. In these applications, the thickness of parts is becoming thinner due to the demand for more complex and smaller part shapes, and it is desirable to reduce warping when the parts are thinned. Furthermore, their use in applications requiring low dielectric constant and low dielectric loss tangent, such as the housings of mobile PCs, tablets, mobile phones, etc. that use radio waves in the megahertz to gigahertz range for communication, has been limited.

[0004] As methods for improving the warping of PAS, there have been proposed, for example, a PPS resin composition obtained by blending PPS, glass flakes, inorganic fillers other than glass flakes, and an olefin resin (see, for example, Patent Document 1), and a polyphenylene sulfide resin composition obtained by blending PPS, glass fiber, an olefin polymer containing a specific functional group, an epoxy resin, glass flakes, and / or calcium carbonate (see, for example, Patent Document 2).

[0005] In addition, several studies have been conducted on PAS resin compositions having good adhesion to metals, and, for example, a resin composition containing (a) PAS, (b) a polar group-containing polyethylene copolymer, and (c) a triazine thiol (see, for example, Patent Document 3), and a resin composition containing (a) PPS, (b) a polar group-containing polyolefin, and (c) a compatibilizer (see, for example, Patent Document 4) have been proposed.

[0006] Furthermore, the low dielectric glass has a glass composition, by weight, of SiO2 53-57%, Al2O3 13-16%, B2O3 15-19.5%, MgO 3% or more but less than 6%, CaO2-5%, TiO2 1-4%, Li2O 0-0.3%, Na2O 0-0.3%, K2O 0-0.5%, and F2 0.2-1%, and has a viscosity μ (poise) of 7-10% MgO+CaO and 0.2-0.5% LiO2+Na2O+K2O. A low dielectric constant glass fiber in which the spinning temperature when logμ=3.0 is 1340°C or less and the amount of B2O3 volatilized during spinning is 4 ppm or less (for example, see Patent Document 5). The glass fiber has a composition by weight of 50-60% SiO2, 10-20% Al2O3, 20-30% B2O3, 0-5% CaO, 0-4% MgO, 0-0.5% Li2O+Na2O+K2O, and 0.5-5% TiO2, and has a dielectric loss tangent of 10×10 at a frequency of 1 MHz. -4 Low dielectric constant glass fibers having the following properties have been proposed (see, for example, Patent Document 6).

[0007] As a glass fiber reinforced resin molded product having a low dielectric constant and a low dielectric tangent, a glass fiber reinforced resin molded product containing glass fiber in a range of 10 to 90 mass % and resin in a range of 90 to 10 mass % relative to the total amount of the glass fiber reinforced resin molded product, the glass fiber contains SiO2 in a range of 52.0 to 57.0 mass %, Al2O3 in a range of 13.0 to 17.0 mass %, B2O3 in a range of 15.0 to 21.5 mass %, MgO in a range of 2.0 to 6.0 mass %, CaO in a range of 2.0 to 6.0 mass %, TiO2 in a range of 1.0 to 4.0 mass %, and F2 less than 1.5 mass %, and the total amount of Li2O, Na2O, and K2O is less than 0.6 mass %, and the glass fiber has a number average fiber length of 30 to 5000 μm (for example, see Patent Document 7).

[0008] In addition, although for different purposes, a PPS resin composition containing a specific PPS and glass fiber having a flat cross-sectional shape (see, for example, Patent Document 8), and an insert molded product of a resin composition containing a PPS resin, glass fiber having a flat cross-sectional shape, and a thermoplastic elastomer and a metal (see, for example, Patent Document 9) have been proposed. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2002-129014 A [Patent Document 2] JP 2005-306926 A [Patent Document 3] JP 2010-070712 A [Patent Document 4] JP 2010-284899 A [Patent Document 5] Patent No. 6352186 [Patent Document 6] Patent No. 3269937 [Patent Document 7] JP 2017-52974 A [Patent Document 8] JP 2006-328291 A [Patent Document 9] JP 2005-161693 A Summary of the Invention [Problem to be solved by the invention]

[0010] However, the resin compositions proposed in Patent Documents 1 and 2 had a problem in terms of warping when used as a component. In addition, the resin compositions proposed in Patent Documents 3 and 4 had good adhesion to metals, but no consideration was given to warping and weather resistance when used as a component, and there was a possibility of problems occurring. Furthermore, Patent Documents 5 and 6 propose low-dielectric constant glass fibers, but they are proposed for reinforcing printed wiring boards for high-density circuits, and there is no consideration or mention of lowering the dielectric constant of polyarylene sulfide. Furthermore, Patent Document 7 proposes a glass fiber-reinforced resin molded product with a low dielectric constant and low dielectric loss tangent, but there is no consideration or mention of lowering the dielectric constant of polyarylene sulfide. And the resin compositions proposed in Patent Documents 8 and 9 had the possibility of having problems with the dielectric constant and dielectric loss tangent. That is, it was generally difficult for these proposed resin compositions to simultaneously achieve low warping when used as a component, good adhesion to metals, low dielectric constant and low dielectric loss tangent, and impact resistance.

[0011] Therefore, the present invention relates to a polyarylene sulfide resin composition which, when used as a component, has a small amount of warping, good adhesion to metal, a low dielectric constant and low dielectric tangent, and also has excellent impact resistance, and a composite in which a polyarylene sulfide resin composition component is integrated with a metal component; more specifically, the present invention relates to a polyarylene sulfide resin composition and a composite made therefrom which, because of these excellent properties, are particularly useful for electrical and electronic components such as the housings of mobile terminal devices such as mobile PCs, tablets, and mobile phones. [Means for solving the problem]

[0012] As a result of intensive research aimed at solving the above problems, the present inventors have found that a resin composition containing a polyarylene sulfide resin, at least an ethylene-based polymer, and a specific glass fiber in a specific blending ratio can become a polyarylene sulfide resin composition that, when used as a component, has low warping, good bonding properties with metals, a low dielectric constant, a low dielectric tangent, and excellent impact resistance, and have thus completed the present invention.

[0013] That is, the present invention relates to a polyarylene sulfide resin composition comprising 30 to 70% by weight of polyarylene sulfide (A), 3 to 20% by weight of an ethylene-based polymer (B), and 30 to 60% by weight of glass fiber (C) having a dielectric constant of 5.5 or less at 2 GHz and a fiber cross-sectional aspect ratio of 2 to 4.

[0014] The present invention will be described in detail below.

[0015] The polyarylene sulfide resin composition of the present invention comprises 30 to 70% by weight of polyarylene sulfide (A), 3 to 20% by weight of an ethylene-based polymer (B), and 30 to 60% by weight of glass fiber (C) having a dielectric constant of 5.5 or less at 2 GHz and a fiber cross-sectional aspect ratio of 2 to 4.

[0016] The polyarylene sulfide (A) constituting the polyarylene sulfide resin composition of the present invention may be any polyarylene sulfide that belongs to the category generally referred to as polyarylene sulfide. Examples of the polyarylene sulfide include homopolymers or copolymers consisting of p-phenylene sulfide units, m-phenylene sulfide units, o-phenylene sulfide units, phenylene sulfide sulfone units, phenylene sulfide ketone units, phenylene sulfide ether units, and biphenylene sulfide units. Specific examples of the polyarylene sulfide include poly(p-phenylene sulfide), polyphenylene sulfide sulfone, polyphenylene sulfide ketone, and polyphenylene sulfide ether. Among these, poly(p-phenylene sulfide) is preferred because it results in a polyarylene sulfide resin composition that is particularly excellent in heat resistance and strength characteristics.

[0017] Furthermore, the polyarylene sulfide (A) is preferably a polyarylene sulfide having a melt viscosity of 50 to 1000 poise measured under conditions of a measuring temperature of 315°C and a load of 10 kg using a high-temperature flow tester equipped with a die having a diameter of 1 mm and a length of 2 mm, and among these, a polyarylene sulfide having a melt viscosity of 100 to 700 poise is preferable, since it is a polyarylene sulfide resin composition having excellent thin-wall fluidity and impact resistance. The polyarylene sulfide (A) can be produced by a method known as a method for producing polyarylene sulfide, and can be obtained, for example, by polymerizing an alkali metal sulfide salt and a polyhalo aromatic compound in a polar solvent. Examples of the polar organic solvents include N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, cyclohexylpyrrolidone, dimethylformamide, and dimethylacetamide. Examples of the alkali metal sulfide salts include anhydrous or hydrated sodium sulfide, rubidium sulfide, and lithium sulfide. Examples of the alkali metal sulfide salts include those obtained by reacting alkali metal hydrosulfide salts with alkali metal hydroxides. Examples of the polyhalo aromatic compounds include p-dichlorobenzene, p-dibromobenzene, p-diiodobenzene, m-dichlorobenzene, m-dibromobenzene, m-diiodobenzene, 4,4'-dichlorodiphenylsulfone, 4,4'-dichlorobenzophenone, 4,4'-dichlorodiphenylether, and 4,4'-dichlorodibiphenyl.

[0018] The polyarylene sulfide (A) may be linear, may be a polyarylene sulfide having a small amount of trihalogen or higher polyhalogen compound added during polymerization to introduce a crosslinked or branched structure, may be a polyarylene sulfide having a molecular chain partially and / or terminally modified with a functional group such as a carboxyl group, a carboxy metal salt, an alkyl group, an alkoxy group, an amino group, or a nitro group, may be a polyarylene sulfide having a heat treatment in a non-oxidizing inert gas such as nitrogen, or may be a mixture of these structures. The polyarylene sulfide (A) may be a polyarylene sulfide having ions, oligomers, and other impurities reduced by deionization (acid washing, hot water washing, etc.) before or after heat curing, or by washing with an organic solvent such as acetone or methyl alcohol. The polyarylene sulfide (A) may be a polyarylene sulfide having a heat treatment in an inert gas or an oxidizing gas after the polymerization reaction is completed to cure the polyarylene sulfide.

[0019] The amount of polyarylene sulfide (A) constituting the polyarylene sulfide resin composition of the present invention is 30 to 70% by weight, and preferably 35 to 65% by weight. If the amount of polyarylene sulfide is less than 30% by weight, the resulting composition will have a high dielectric constant and dielectric loss tangent. On the other hand, if the amount of polyarylene sulfide is more than 70% by weight, the resulting composition will be prone to warping when used as a member.

[0020] The ethylene-based polymer (B) constituting the polyarylene sulfide resin composition of the present invention improves the metal bonding properties of the polyarylene sulfide resin composition, and is preferably at least one modified ethylene-based polymer selected from the group consisting of ethylene-α,β-unsaturated carboxylic acid alkyl ester-maleic anhydride copolymers, ethylene-α,β-unsaturated carboxylic acid glycidyl ester copolymers, ethylene-α,β-unsaturated carboxylic acid glycidyl ester-vinyl acetate copolymers, ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid alkyl ester copolymers, and maleic anhydride-grafted ethylene-α-olefin copolymers.

[0021] As the ethylene-α,β-unsaturated carboxylic acid alkyl ester-maleic anhydride copolymer, any one that belongs to this category may be used, and among them, since the obtained polyarylene sulfide resin composition has excellent bonding properties with metals, etc., it is preferable that the ethylene residue unit:α,β-unsaturated carboxylic acid alkyl ester residue unit:maleic anhydride residue unit (weight ratio) is in the range of 50 to 98:40 to 1:10 to 1. Specific examples of the ethylene-α,β-unsaturated carboxylic acid alkyl ester-maleic anhydride copolymer include (trade name) Bondine LX4110 (manufactured by Arkema Co., Ltd.), (trade name) Bondine TX8030 (manufactured by Arkema Co., Ltd.), (trade name) Bondine AX8390 (manufactured by Arkema Co., Ltd.), etc.

[0022] As the ethylene-α,β-unsaturated carboxylic acid glycidyl ester copolymer, any one that belongs to this category may be used, and among them, since the obtained polyarylene sulfide resin composition has excellent bonding properties with metals, etc., it is preferable that the ethylene residue unit:α,β-unsaturated carboxylic acid glycidyl ester residue unit (weight ratio) is in the range of 85 to 99: 15 to 1. Specific examples of the ethylene-α,β-unsaturated carboxylic acid glycidyl ester copolymer include (trade name) Bondine AX8840 (manufactured by Arkema Co., Ltd.) and (trade name) Bondfast E (manufactured by Sumitomo Chemical Co., Ltd.).

[0023] The ethylene-α,β-unsaturated carboxylic acid glycidyl ester-vinyl acetate copolymer may be any copolymer that falls within this category, and since the resulting polyarylene sulfide resin composition has excellent bonding properties with metals, it is preferable that the weight ratio of ethylene residue units:α,β-unsaturated carboxylic acid glycidyl ester residue units:vinyl acetate residue units is in the range of 50 to 98:15 to 1:35 to 1. Specific examples of the ethylene-α,β-unsaturated carboxylic acid glycidyl ester-vinyl acetate copolymer include (trade name) Bondfast 2B (manufactured by Sumitomo Chemical Co., Ltd.) and (trade name) Bondfast 7B (manufactured by Sumitomo Chemical Co., Ltd.).

[0024] As the ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid alkyl ester copolymer, any one that belongs to this category may be used, and among them, since the obtained polyarylene sulfide resin composition has excellent bonding properties with metals, etc., it is preferable that the ethylene residue unit:α,β-unsaturated carboxylic acid glycidyl ester residue unit:α,β-unsaturated carboxylic acid alkyl ester residue unit (weight ratio) is in the range of 50 to 98:10 to 1:40 to 1. Specific examples of the ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid alkyl ester copolymer include (trade name) Bondfast 7L (manufactured by Sumitomo Chemical Co., Ltd.), (trade name) Bondfast 7M (manufactured by Sumitomo Chemical Co., Ltd.), (trade name) LOTADER AX8700 (manufactured by Arkema Co., Ltd.), and (trade name) LOTADER AX8750 (manufactured by Arkema Co., Ltd.).

[0025] The maleic anhydride grafted ethylene-α-olefin copolymer may be any one that falls within this category, and among them, since the resulting polyarylene sulfide resin composition has excellent bonding properties with metals, it is preferable that the ratio of ethylene residue units:α-olefin residue units:maleic anhydride residue units (weight ratio) is in the range of 50 to 98: 45 to 1: 5 to 1, and specific examples include maleic anhydride grafted linear low-density polyethylene, maleic anhydride grafted ethylene-propylene rubber, etc. The maleic anhydride grafted ethylene-α-olefin copolymer can be obtained, for example, by carrying out a grafting reaction in the coexistence of an ethylene-α-olefin copolymer, a peroxide, and maleic anhydride.

[0026] The α-olefin constituting the modified ethylene polymer refers to an α-olefin having 3 or more carbon atoms, and examples thereof include propylene, butene-1, 4-methyl-pentene-1, hexene-1, and octene-1. Examples of the α,β-unsaturated carboxylic acid alkyl ester include alkyl esters of acrylic acid and methacrylic acid, and more specifically, examples thereof include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, t-butyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, and t-butyl methacrylate. Examples of the α,β-unsaturated carboxylic acid glycidyl ester include acrylic acid glycidyl ester and methacrylic acid glycidyl ester.

[0027] The blending amount of the ethylene polymer (B) is 3 to 20% by weight, preferably 4 to 18% by weight, since the polyarylene sulfide resin composition has particularly excellent metal bonding property and molding flowability. If the blending amount of the ethylene polymer (B) is less than 3% by weight, the resulting resin composition has poor impact resistance and bonding property with metal when made into a composite. On the other hand, if the blending amount exceeds 20% by weight, the resulting resin composition has a high dielectric constant and dielectric loss tangent, which is not preferable.

[0028] The glass fiber (C) constituting the polyarylene sulfide resin composition of the present invention may be any (flat) glass fiber having a dielectric constant of 5.5 or less at 2 GHz and a fiber cross-sectional aspect ratio of 2 to 4, and the type of the glass fiber (C) is preferably NE glass or D glass having a dielectric constant of 5.5 or less at 2 GHz, and among these, NE glass is particularly preferred since it results in a polyarylene sulfide resin composition with excellent mechanical strength. Here, if the glass fiber has a dielectric constant of more than 5.5 at 2 GHz, the resulting resin composition will have a high dielectric constant, and there is a high possibility that its use as an electric / electronic device part will be restricted.

[0029] The cross-sectional shape of the glass fiber (C) is a (flat) glass fiber having a fiber cross-sectional aspect ratio of 2 to 4, and specific cross-sectional shapes are preferably oval, elliptical, semicircular, cocoon-shaped, rectangular, or similar shapes. Here, when the fiber cross-sectional aspect ratio is less than 2, the amount of warping of the obtained molded product becomes large. On the other hand, when it exceeds 4, problems may occur in flowability and molding processability. And, as the fiber diameter of the glass fiber (C), the short diameter of the fiber cross section is preferably 6 to 16 μm, since it becomes a polyarylene sulfide resin composition having particularly excellent mechanical strength and molding flowability.

[0030] The glass fiber (C) may be in the form of chopped strand, milled fiber, roving, etc., and is preferably chopped strand, since it is easy to handle when it is made into a polyarylene sulfide resin composition. An example of a chopped strand having a dielectric constant of 5.5 or less at 2 GHz and a fiber cross-sectional aspect ratio of 4 is (product name) ECS309A-3-M4 (manufactured by Taishan Co., Ltd.). If necessary, these glass fibers (C) may be surface-treated in advance with a functional compound or polymer such as an epoxy compound, an isocyanate compound, a silane compound, or a titanate compound.

[0031] The blending amount of the glass fiber (C) is 30 to 60% by weight. If it is less than 30% by weight, the resulting resin composition is likely to warp when used as a part. On the other hand, if it exceeds 60% by weight, the resulting resin composition has a high dielectric constant and dielectric loss tangent.

[0032] Furthermore, since the polyarylene sulfide resin composition of the present invention exhibits particularly excellent performance in terms of electrical properties and can be used as a material for various electric and electronic components, it is preferable that the composition has a dielectric constant of 3.5 or less and a dielectric dissipation factor of 0.010 or less, measured at a measurement frequency of 2 GHz in accordance with JIS C-2565.

[0033] The polyarylene sulfide resin composition of the present invention is particularly excellent in moldability, and is therefore preferably further formulated with a release agent (D). The release agent (D) is preferably one or more selected from, for example, polyethylene wax, polypropylene wax, fatty acid amide lubricants, and carnauba wax, and commercially available products can be used as the polyethylene wax, polypropylene wax, fatty acid amide lubricants, and carnauba wax. The fatty acid amide lubricants include polycondensates of higher fatty acid amides, ethylene bisstearamide, higher fatty acids, and diamines, and any lubricants that fall within this category can be used, for example, Light Amide WH-255 (manufactured by Kyoeisha Chemical Co., Ltd.), which is a polycondensate of stearic acid, sebacic acid, and ethylenediamine. The carnauba wax can be any lubricant that is generally called carnauba wax, and for example, Refined Carnauba Powder No. 1 (manufactured by Nikko Rica Co., Ltd.). The amount of the release agent (D) to be added is preferably 0.1 to 3 parts by weight per 100 parts by weight of the total of the polyarylene sulfide (A), the ethylene polymer (B) and the glass fiber (C).

[0034] The polyarylene sulfide resin composition of the present invention may be one to which whiskers such as carbon fibers, silicon nitride whiskers, basic magnesium sulfate whiskers, barium titanate whiskers, potassium titanate whiskers, silicon carbide whiskers, boron whiskers, zinc oxide whiskers, etc.; inorganic fibers such as rock wool, zirconia, barium titanate, silicon carbide, silica, blast furnace slag, etc.; organic fibers such as wholly aromatic polyamide fibers, phenolic resin fibers, wholly aromatic polyester fibers, etc.; and mineral fibers such as wollastonite, magnesium oxysulfate, etc. are added, so long as the effects of the present invention are not impaired. Alternatively, the polyarylene sulfide resin composition of the present invention may be one to which calcium carbonate, lithium carbonate, magnesium carbonate, zinc carbonate, mica, silica, talc, clay, calcium sulfate, kaolin, wollastonite, zeolite, silicon oxide, magnesium oxide, zirconium oxide, tin oxide, magnesium silicate, calcium silicate, calcium phosphate, magnesium phosphate, carbon black, hydrotalcite, glass powder, glass balloons, and glass flakes are added, so long as the effects of the present invention are not impaired.

[0035] Furthermore, the polyarylene sulfide resin composition of the present invention may contain one or more of conventional additives, such as a crystal nucleating agent such as talc, kaolin, or silica; a plasticizer such as a polyalkylene oxide oligomer compound, a thioether compound, an ester compound, or an organic phosphorus compound; an antioxidant; a heat stabilizer; a lubricant; a foaming agent; or a silane coupling agent, within the scope of the invention.

[0036] Furthermore, the polyarylene sulfide resin composition of the present invention may be prepared by mixing one or more of various thermosetting resins and thermoplastic resins, such as epoxy resins, cyanate ester resins, phenolic resins, polyimides, silicone resins, polyesters, polyamides, polyphenylene oxides, polycarbonates, polysulfones, polyetherimides, polyethersulfones, polyetherketones, polyetheretherketones, polyamideimides, polyamide-based elastomers, polyester-based elastomers, and polyalkylene oxides, within the scope of the object of the present invention.

[0037] The method for producing the polyarylene sulfide resin composition of the present invention is not particularly limited, and a method known as a general mixing and kneading method can be used. For example, a method of blending all raw materials and melt-kneading them; a method of blending a part of the raw materials and then melt-kneading them, and then blending the remaining raw materials and melt-kneading them; or a method of blending a part of the raw materials and then mixing the remaining raw materials using a side feeder while melt-kneading them with a single-screw or twin-screw extruder. In addition, a small amount of added components may be used by blending other components by the above method or the like, pelletizing them, and then adding them before molding. As a method for melt-kneading, a conventionally used heating and melt-kneading method can be used, for example, a heating and melt-kneading method using a single-screw or twin-screw extruder, a kneader, a mill, a Brabender, or the like. In particular, a melt-kneading method using a twin-screw extruder with excellent kneading ability is preferable. In addition, the kneading temperature in this case is not particularly limited, and can usually be selected from 260 to 350°C.

[0038] The polyarylene sulfide resin composition of the present invention exhibits excellent impact resistance and has excellent bonding properties with metals (components), and therefore can be used as a metal component-polyarylene sulfide resin composition component composite in which a polyarylene sulfide resin composition component and a metal component are directly integrated by injection molding.

[0039] The metal member may be made of any material as long as it falls within the category of metal members, and among these, metal members made of aluminum, aluminum alloy, copper, copper alloy, magnesium, magnesium alloy, iron, titanium, titanium alloy, or stainless steel are preferred, since they can be adapted to various applications when made into a polyarylene sulfide resin composition member composite.

[0040] The metal member is preferably a metal member whose surface has been physically and / or chemically treated, and by carrying out the physical and / or chemical treatment, the metal member has excellent adhesion, bonding and airtightness when directly integrated with the polyarylene sulfide resin composition member. Any method can be used to physically and / or chemically treat the surface of the metal member, and among them, a composite with particularly excellent bonding and adhesion between the metal member and the polyarylene sulfide resin composition member can be obtained. Examples of the physical treatment include a method of contacting or colliding fine solid particles with the surface, and a method of irradiating high-energy electromagnetic rays, and more specifically, a sandblasting treatment, a liquid honing treatment, a laser processing treatment, and the like. Furthermore, examples of the abrasives used in the sandblasting treatment and the liquid honing treatment include sand, steel grid, steel shot, cut wire, alumina, silicon carbide, metal slag, glass beads, plastic beads, and the like. Examples of laser processing include the methods proposed in WO2007 / 072603, JP2015-142960A, and JP2016-132131A, and examples of methods of irradiating high-energy electromagnetic rays include the method proposed in JP2011-140167A.

[0041] In addition, since a composite having particularly excellent bonding and adhesion between the metal member and the polyarylene sulfide resin composition member is obtained, examples of chemical treatments that can be mentioned include anodizing and chemical treatment with an aqueous acid or alkali solution.

[0042] The anodizing treatment may be, for example, a method in which an electrochemical reaction is carried out in an electrolytic solution using a metal member as an anode to form an oxide film on the surface, and a method generally known as anodizing in the field of plating and the like can be used. More specifically, examples of the anodizing treatment include 1) a direct current electrolysis method in which electrolysis is carried out by applying a constant direct current voltage, and 2) a bipolar electrolysis method in which electrolysis is carried out by applying a voltage in which an alternating current component is superimposed on a direct current component. Specific examples of the anodizing treatment include the method proposed in WO2004 / 055248 and the like.

[0043] The method of chemically treating the metal member with an aqueous acid or alkali solution may be, for example, a method of immersing the metal member in an aqueous acid or alkali solution to chemically treat the surface of the metal member. Examples of the aqueous acid or alkali solution include phosphoric acid and other phosphoric acid compounds; chromic acid and other chromic acid compounds; hydrofluoric acid and other hydrofluoric acid compounds; nitric acid and other nitric acid compounds; hydrochloric acid and other hydrochloric acid compounds; sulfuric acid and other sulfuric acid compounds; aqueous alkali solutions such as sodium hydroxide and ammonia solution; trichloroethylene and the like. Examples of the method include a method of chemically treating the surface with an aqueous solution of zincthiol or a triazinethiol derivative. More specific examples include the methods proposed in JP-A-10-096088, JP-A-10-056263, JP-A-04-032585, JP-A-04-032583, JP-A-02-298284, WO2009 / 151099, WO2011 / 104944, and JP-A-2010-254793.

[0044] The physical treatment and / or chemical treatment may be performed alone or in combination. For example, a metal member whose surface has been subjected to a physical treatment and then a chemical treatment may be used to form a metal member-polyarylene sulfide resin composition member composite.

[0045] As a method for producing the metal member-polyarylene sulfide resin composition member composite, any method can be used as long as it is possible to directly integrate the metal member whose surface has been physically and / or chemically treated with the polyarylene sulfide resin composition member by injection molding. Among them, it is preferable to integrate them by injection insert molding, since it is possible to produce a composite efficiently. As the injection insert molding method, for example, a method can be mentioned in which a metal member whose metal surface has been physically and / or chemically treated is mounted in a mold, the metal member is filled with a molten polyarylene sulfide resin composition to form a polyarylene sulfide resin composition member, and the metal member and the polyarylene sulfide resin composition member are directly integrated to form a composite. In this case, the melting temperature of the polyarylene sulfide resin composition can be 280 to 340 ° C., and as a molding machine for performing insert molding, it is preferable to perform insert injection molding using an injection molding machine, since it is particularly excellent in productivity.

[0046] The shape of the metal member-polyarylene sulfide resin composition member composite is preferably such that the thickness of the composite is in the range of 0.5 to 5 mm and the ratio of the length and width to the thickness is at least 10, since this provides excellent filling properties for the polyarylene sulfide resin composition when directly integrated by injection molding and results in a composite with little warping when used as a member. Examples of parts having this shape include housings for mobile terminal devices such as mobile personal computers, tablets, and mobile phones, and in-vehicle capacitor cases.

[0047] The polyarylene sulfide resin composition of the present invention has low dielectric constant and dielectric tangent, particularly in the high frequency range, and exhibits little warping when used as a component, and also has good bonding properties with metal components and excellent impact resistance. Therefore, the composition is suitably used for electrical and electronic components such as housings for mobile terminal devices, where thinner components are desired to meet the needs for more complex part shapes and smaller size, or automotive electrical components. Effect of the Invention

[0048] The present invention provides a polyarylene sulfide resin composition which has a low dielectric constant and a low dielectric loss tangent and therefore excellent radio wave transmittance in the megahertz to gigahertz bands, has a small amount of warping when used as a component, has good bonding properties with metal components, and is also excellent in impact resistance. The composition is useful for electronic / electrical component applications such as housings for mobile terminal devices such as mobile PCs, tablets, and mobile phones, and for electrical component applications such as automotive electrical components. EXAMPLES

[0049] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0050] The polyarylene sulfide (A), ethylene polymer (B), glass fiber (C) and release agent (D) used in the examples and comparative examples are shown below.

[0051] <Polyarylene sulfide (A)> Poly(p-phenylene sulfide) (A-1) (hereinafter referred to as PPS (A-1)): melt viscosity 500 poise. Poly(p-phenylene sulfide) (A-2) (hereinafter referred to as PPS (A-2)): melt viscosity 150 poise. Poly(p-phenylene sulfide) (A-3) (hereinafter referred to as PPS (A-3)): melt viscosity 400 poise.

[0052] <Ethylene-based polymer (B)> Ethylene-α,β-unsaturated carboxylic acid alkyl ester-maleic anhydride copolymer (B-1) (hereinafter referred to as ethylene-based copolymer (B-1)): manufactured by Arkema Co., Ltd., (product name) Bondine AX8390. Ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid alkyl ester copolymer (B-2) (hereinafter referred to as ethylene copolymer (B-2)): manufactured by Sumitomo Chemical Co., Ltd., (product name) Bondfast 7M. Ethylene-α,β-unsaturated carboxylic acid glycidyl ester copolymer (B-3) (hereinafter referred to as ethylene-based copolymer (B-3)): manufactured by Arkema Co., Ltd., (product name) Bondine AX8840. Ethylene-α,β-unsaturated carboxylic acid glycidyl ester-vinyl acetate copolymer (B-4) (hereinafter referred to as ethylene-based copolymer (B-4)): manufactured by Sumitomo Chemical Co., Ltd., (product name) Bondfast 7B.

[0053] <Glass fiber (C)> Glass fiber (C-1); Taishan chopped strand, (product name) ECS309A-3-M4, dielectric constant at a measurement frequency of 2 GHz is 4.5, and aspect ratio of fiber cross section is 4. Glass fiber (C-2): chopped strand manufactured by Nitto Boseki Co., Ltd., (product name) CSG-3PA 830, dielectric constant at a measurement frequency of 2 GHz of 6.8, aspect ratio of fiber cross section of 4. Glass fiber (C-3); Taishan chopped strand, (product name) TLD-T443, dielectric constant 4.5 at a measurement frequency of 2 GHz, aspect ratio of fiber cross section 1.

[0054] <Release agent (D)> Fatty acid amide lubricant (D-1) (hereinafter, may be referred to as release agent (D-1)); product name: Lightamide WH-255, manufactured by Kyoeisha Chemical Co., Ltd. Carnauba wax (D-2) (hereinafter, may be referred to as release agent (D-2)); product name: Refined Carnauba Powder No. 1, manufactured by Nikko Rica Corporation.

[0055] <Synthesis Example 1 (Synthesis of PPS (A-1))> In a 50-liter autoclave equipped with a stirrer, 6214 g of flake sodium sulfide (Na2S·2.9H2O) and 17000 g of N-methyl-2-pyrrolidone were charged, and the temperature was gradually raised to 205°C while stirring under a nitrogen stream, and 1355 g of water was distilled off. After cooling the system to 140°C, 7150 g of p-dichlorobenzene, 47 g of 3,5-dichloroaniline, and 5000 g of N-methyl-2-pyrrolidone were added, and the system was sealed under a nitrogen stream. The system was heated to 225°C over 2 hours, polymerized at 225°C for 2 hours, then heated to 250°C over 30 minutes, and polymerized at 250°C for another 3 hours. After the polymerization was completed, the system was cooled to room temperature, and the polymer was isolated by centrifugation. The solid polymer was repeatedly washed with warm water and dried overnight at 100°C to obtain an amino group-substituted poly(p-phenylene sulfide) with a melt viscosity of 250 poise. The dried amino group-substituted poly(p-phenylene sulfide) was then loaded into a batch-type rotary kiln-type calciner and cured for 5 hours at 250°C in a nitrogen atmosphere to obtain PPS (A-1) with a melt viscosity of 500 poise and an amino group content of 0.6 mol% relative to the phenyl groups.

[0056] <Synthesis Example 2 (Synthesis of PPS (A-2))> In a 15-liter autoclave equipped with a stirrer, 1814 g of flake sodium sulfide (Na2S·2.9H2O), 48 g of 30% caustic soda solution (30%NaOHaq), and 3679 g of N-methyl-2-pyrrolidone were charged, and the mixture was gradually heated to 200°C while stirring under a nitrogen stream, and 380 g of water was distilled off. After cooling to 190°C, 2107 g of p-dichlorobenzene and 985 g of N-methyl-2-pyrrolidone were added, and the system was sealed under a nitrogen stream. The system was heated to 225°C over 2 hours, polymerized at 225°C for 1 hour, then heated to 250°C over 25 minutes, and polymerized at 250°C for 3 hours. After polymerization, N-methyl-2-pyrrolidone was recovered from the polymerization slurry by distillation under reduced pressure. The final temperature was 170°C and the pressure was 4.7 kPa. The resulting cake was washed by adding 80°C hot water to a slurry concentration of 20%, and hot water was added again in the same manner to raise the temperature to 175°C, washing the poly(p-phenylene sulfide) twice in total. The resulting polyphenylene sulfide was dried at 105°C for a whole day and night. The dried polyphenylene sulfide was then loaded into a batch-type rotary kiln-type calciner, heated to 235°C in a nitrogen atmosphere, and held for 1 hour to perform a curing treatment, thereby obtaining PPS (A-2) with a melt viscosity of 150 poise.

[0057] <Synthesis Example 3 (Synthesis of PPS (A-3))> In a 15-liter autoclave equipped with a stirrer, 1814g of flake sodium sulfide (Na2S·2.9H2O), 8.7g of granular caustic soda (100% NaOH: Wako Pure Chemical special grade), and 3232g of N-methyl-2-pyrrolidone were charged, and the mixture was gradually heated to 200°C while stirring under a nitrogen stream, and 340g of water was distilled off. After cooling to 190°C, 2107g of p-dichlorobenzene and 1783g of N-methyl-2-pyrrolidone were added, and the system was sealed under a nitrogen stream. The system was heated to 225°C over 2 hours, polymerized at 225°C for 1 hour, then heated to 250°C over 25 minutes, and polymerized at 250°C for 2 hours. Next, 509g of distilled water was injected into the system at 250°C, and the system was heated to 255°C and polymerized for another 1 hour. After polymerization, N-methyl-2-pyrrolidone was recovered from the polymerization slurry by distillation under reduced pressure. The final temperature reached was 170°C and the pressure was 4.7 kPa. The resulting cake was washed with 80°C hot water to a slurry concentration of 20%, and hot water was added again in the same manner to raise the temperature to 175°C, washing the poly(p-phenylene sulfide) twice in total. The resulting poly(p-phenylene sulfide) was dried at 105°C overnight to obtain PPS (A-3) with a melt viscosity of 400 poise.

[0058] The evaluation and measurement methods for the obtained polyarylene sulfide resin and polyarylene sulfide resin composition are shown below.

[0059] ~Melt viscosity measurement of polyarylene sulfide~ The melt viscosity was measured using a high-temperature flow tester (manufactured by Shimadzu Corporation, product name CFT-500) equipped with a die having a diameter of 1 mm and a length of 2 mm, under conditions of a measurement temperature of 315° C. and a load of 10 kg.

[0060] ~Measurement of dielectric constant and dielectric tangent~ The polyarylene sulfide resin composition was injection molded by an injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., (product name) SE-75D) with a cylinder temperature of 310 ° C. and a mold temperature of 135 ° C. to prepare a molded plate of 70 mm × 70 mm × 1 mm thickness, and a test piece for measuring the dielectric constant of 70 mm × 3 mm × 1 mm thickness was prepared from this molded plate by cutting processing. The dielectric constant and dielectric loss tangent of this test piece were measured at a measurement frequency of 2 GHz using a dielectric constant measuring device (manufactured by AET Corporation, (product name) Cavity Resonator) in accordance with JIS C-2565. A dielectric constant of 3.5 or less and a dielectric loss tangent of 0.010 or less were judged to have sufficiently low dielectric properties for practical use.

[0061] ~Impact resistance measurement~ A test piece for measuring Charpy impact strength was prepared from the polyarylene sulfide resin composition using an injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., product name: SE-75S) with a cylinder temperature of 310°C and a mold temperature of 135°C. A notch was made using a notching machine (manufactured by Toyo Seiki Seisakusho Co., Ltd., product name: A-3 type), and the impact strength was measured in accordance with ISO179 using a Charpy impact tester (manufactured by Toyo Seiki Seisakusho Co., Ltd., product name: DG-CB type). The Charpy impact strength was measured at 10 kJ / m 2 Anything exceeding this was judged to have sufficiently high impact properties for practical use.

[0062] ~Evaluation of metal bonding and warpage~ A metal plate (70 mm (longitudinal) x 70 mm (lateral) x 1 mm (thickness) or 20 mm (longitudinal) x 20 mm (lateral) x 1 mm (thickness)) having a surface that had been subjected to a physical and / or chemical treatment was placed in an injection molding machine mold with the mold temperature set to 150°C, and a polyarylene sulfide resin composition was placed in the hopper of an injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., (product name) SE75S) heated to 310°C, and injection insert molding was performed to obtain a metal member-polyarylene sulfide resin composition member composite of 70 mm x 70 mm x 2 mm (thickness) (the ratios of the vertical and horizontal sizes to the thickness direction of the laminate layer were 35 each) or 20 mm x 20 mm x 2 mm (thickness) (the ratios of the vertical and horizontal sizes to the thickness direction of the laminate layer were 10 each).

[0063] The interface of the metal member-polyarylene sulfide resin composition member composite 24 hours after molding was visually evaluated. ◯: No peeling was observed at the interface of the metal member-polyarylene sulfide resin composition member composite. ×: Peeling was observed at the interface of the metal member-polyarylene sulfide resin composition member composite.

[0064] Furthermore, the metal member-polyarylene sulfide resin composition member composite 24 hours after molding was evaluated using a 3D scanner type coordinate measuring machine (Keyence Corporation, product name VL-350) by setting three vertices of the composite as reference points and the deviation of the remaining vertex from the reference plane as the amount of warping. A deviation of less than 1 mm was determined to be practically low warping.

[0065] Example 1 85.8% by weight of PPS (A-1) obtained in Synthesis Example 1, 13.4% by weight of ethylene copolymer (B-1), and 0.8% by weight of release agent (D-1) were mixed uniformly in advance and fed into the hopper of a twin-screw extruder (Toshiba Machine, (product name) TEM-35-102B) heated to a cylinder temperature of 300°C. On the other hand, glass fiber (C-1) was fed from the hopper of the side feeder of the twin-screw extruder, melt-kneaded, and pelletized to obtain a polyarylene sulfide resin composition. The composition ratio of the polyarylene sulfide resin composition at that time was 51.5% by weight of PPS (A-1), 8% by weight of ethylene copolymer (B-1), 40% by weight of glass fiber (C-1), and 0.5% by weight of release agent (D-1).

[0066] On the other hand, a flat plate (70 mm × 70 mm × 1 mm (thickness)) made of an aluminum alloy (A5052) was immersed in acetone to clean the surface, and then the test piece was immersed in a 1% by weight sodium hydroxide aqueous solution, then in a 10% by weight sulfuric acid aqueous solution, and further in a 15% by weight sulfuric acid aqueous solution at a current density of 0.5 A / cm 3The aluminum alloy surface was chemically treated by anodizing to obtain an aluminum alloy (A5052) plate.

[0067] The obtained aluminum alloy (A5052) plate was placed in an injection molding machine mold set at a mold temperature of 150°C, and the obtained polyarylene sulfide resin composition was poured into the hopper of an injection molding machine (manufactured by Sumitomo Heavy Industries, product name: SE75S) heated to 310°C, and injection insert molding was performed to obtain an aluminum alloy part-polyarylene sulfide resin composition part composite measuring 70 mm x 70 mm x 2 mm (thickness) (the ratios of the vertical and horizontal sizes to the thickness direction of the laminate layer were each 35).

[0068] The obtained polyarylene sulfide resin composition and the aluminum alloy member-polyarylene sulfide resin composition member composite were evaluated for dielectric constant, dielectric loss tangent, impact resistance, metal bondability, and amount of displacement. The evaluation results are shown in Table 1.

[0069] The obtained polyarylene sulfide resin composition and aluminum alloy member-polyarylene sulfide resin composition member composite had good metal bonding properties and warpage, and also exhibited practically sufficient values ​​for dielectric constant, dielectric loss tangent, and impact resistance.

[0070] Example 2 87.3% by weight of PPS (A-2) obtained in Synthesis Example 2, 11.1% by weight of ethylene copolymer (B-2), and 1.6% by weight of release agent (D-2) were mixed uniformly in advance and fed into the hopper of a twin-screw extruder (Toshiba Machine, (product name) TEM-35-102B) heated to a cylinder temperature of 300°C. On the other hand, glass fiber (C-1) was fed from the hopper of the side feeder of the twin-screw extruder, melt-kneaded, and pelletized to obtain a polyarylene sulfide resin composition. The composition ratio of the polyarylene sulfide resin composition at that time was 39.3% by weight of PPS (A-2), 5% by weight of ethylene copolymer (B-2), 55% by weight of glass fiber (C-1), and 0.7% by weight of release agent (D-2).

[0071] On the other hand, an aluminum die-cast alloy (ADC12) plate (70 mm × 70 mm × 1 mm (thickness)) was immersed in acetone to clean the surface, and then the test piece was subjected to laser treatment in which a laser with a wavelength of 1.064 μm was used to scan the plate 120,000 times in the orthogonal direction at a hatching width of 0.2 mm, a frequency of 6 KHz, and a speed of 100 mm / sec, thereby obtaining an aluminum die-cast alloy (ADC12) plate with a physically treated aluminum die-cast alloy surface.

[0072] The obtained aluminum die-cast alloy (ADC12) plate was placed in an injection molding machine mold with the mold temperature set to 150°C, and the obtained polyarylene sulfide resin composition was poured into the hopper of an injection molding machine (manufactured by Sumitomo Heavy Industries, product name: SE75S) heated to 310°C, and injection insert molding was performed to obtain an aluminum die-cast alloy part-polyarylene sulfide resin composition part composite measuring 70 mm x 70 mm x 2 mm (thickness) (ratio of size in the vertical and horizontal directions to the thickness direction of the laminate layer: 35).

[0073] The dielectric constant, dielectric loss tangent, impact resistance, metal bondability, and amount of displacement of the obtained polyarylene sulfide resin composition and the aluminum die-cast alloy member-polyarylene sulfide resin composition member composite were evaluated. The evaluation results are shown in Table 1.

[0074] The obtained polyarylene sulfide resin composition and the aluminum die-cast alloy member-polyarylene sulfide resin composition member composite had good metal bonding properties and warpage, and also showed practically sufficient values ​​for dielectric constant, dielectric loss tangent, and impact resistance.

[0075] Example 3 71.4% by weight of PPS (A-1) obtained in Synthesis Example 1, 27.7% by weight of ethylene copolymer (B-3), and 0.9% by weight of release agent (D-1) were mixed uniformly in advance and fed into the hopper of a twin-screw extruder (Toshiba Machine, (product name) TEM-35-102B) heated to a cylinder temperature of 300°C. On the other hand, glass fiber (C-1) was fed from the hopper of the side feeder of the twin-screw extruder, melt-kneaded, and pelletized to obtain a polyarylene sulfide resin composition. The composition ratio of the polyarylene sulfide resin composition at that time was 46.4% by weight of PPS (A-1), 18.0% by weight of ethylene copolymer (B-3), 35% by weight of glass fiber (C-1), and 0.6% by weight of release agent (D-1).

[0076] On the other hand, an aluminum alloy (A6063) plate (70 mm × 70 mm × 1 mm (thickness)) was immersed in acetone to clean the surface, and then the test piece was subjected to liquid honing treatment with #800 alumina and then with #2000 alumina, thereby obtaining an aluminum alloy (A6063) plate with a physically treated aluminum alloy surface.

[0077] The obtained aluminum alloy (A6063) plate was placed in an injection molding machine mold set at a mold temperature of 150°C, and the obtained polyarylene sulfide resin composition was poured into the hopper of an injection molding machine (manufactured by Sumitomo Heavy Industries, product name: SE75S) heated to 310°C, and injection insert molding was performed to obtain an aluminum alloy part-polyarylene sulfide resin composition part composite measuring 70 mm x 70 mm x 2 mm (thickness) (the ratio of the size in the vertical and horizontal directions to the thickness direction of the laminate layer is 35).

[0078] The obtained polyarylene sulfide resin composition and the aluminum alloy member-polyarylene sulfide resin composition member composite were evaluated for dielectric constant, dielectric loss tangent, impact resistance, metal bondability, and amount of displacement. The evaluation results are shown in Table 1.

[0079] The obtained polyarylene sulfide resin composition and aluminum alloy member-polyarylene sulfide resin composition member composite had good metal bonding properties and warpage, and also exhibited practically sufficient values ​​for dielectric constant, dielectric loss tangent, and impact resistance.

[0080] Example 4 80% by weight of PPS (A-3) obtained in Synthesis Example 3, 18.2% by weight of ethylene copolymer (B-4), and 1.8% by weight of release agent (D-2) were mixed uniformly in advance and fed into the hopper of a twin-screw extruder (Toshiba Machine, (product name) TEM-35-102B) heated to a cylinder temperature of 300°C. On the other hand, glass fiber (C-1) was fed from the hopper of the side feeder of the twin-screw extruder, melt-kneaded, and pelletized to obtain a polyarylene sulfide resin composition. The composition ratio of the polyarylene sulfide resin composition at that time was 44% by weight of PPS (A-3), 10% by weight of ethylene copolymer (B-4), 45% by weight of glass fiber (C-1), and 1% by weight of release agent (D-1).

[0081] On the other hand, a stainless steel (SUS316) plate (70 mm x 70 mm x 1 mm (thickness)) was immersed in acetone to clean the surface, and then the test piece was subjected to laser treatment in which a laser with a wavelength of 1.064 μm was used to scan the plate 120,000 times in the orthogonal direction with a hatching width of 0.2 mm, a frequency of 6 KHz, and a speed of 200 mm / sec, thereby obtaining a stainless steel (SUS316) plate with a physically treated stainless steel surface.

[0082] The obtained stainless steel (SUS316) plate was placed in an injection molding machine mold with the mold temperature set to 150°C, and the obtained polyarylene sulfide resin composition was placed into the hopper of an injection molding machine (manufactured by Sumitomo Heavy Industries, product name: SE75S) heated to 310°C, and injection insert molding was performed to obtain a stainless steel member-polyarylene sulfide resin composition member composite measuring 70 mm x 70 mm x 2 mm (thickness) (size ratio of the vertical and horizontal directions to the thickness direction of the laminate layer: 35).

[0083] The obtained polyarylene sulfide resin composition and the stainless steel member-polyarylene sulfide resin composition member composite were evaluated for dielectric constant, dielectric loss tangent, impact resistance, metal bondability, and amount of displacement. The evaluation results are shown in Table 1.

[0084] The obtained polyarylene sulfide resin composition and the stainless steel member-polyarylene sulfide resin composition member composite had good metal bonding properties and warpage, and also exhibited practically sufficient values ​​for dielectric constant, dielectric loss tangent, and impact resistance.

[0085] Example 5 91.4% by weight of PPS (A-2) obtained in Synthesis Example 2, 8% by weight of ethylene copolymer (B-1), and 0.6% by weight of release agent (D-2) were mixed uniformly in advance and fed into the hopper of a twin-screw extruder (Toshiba Machine, (product name) TEM-35-102B) heated to a cylinder temperature of 300°C. On the other hand, glass fiber (C-1) was fed from the hopper of the side feeder of the twin-screw extruder, melt-kneaded, and pelletized to obtain a polyarylene sulfide resin composition. The composition ratio of the polyarylene sulfide resin composition at that time was 45.7% by weight of PPS (A-2), 4.0% by weight of ethylene copolymer (B-1), 50% by weight of glass fiber (C-1), and 0.3% by weight of release agent (D-2).

[0086] On the other hand, an aluminum (A1050) plate (70 mm × 70 mm × 1 mm (thickness)) was immersed in ethanol to clean the surface, and then the test piece was roughened by sandblasting using 0.1 mm and then 0.01 mm alumina powder. The test piece was then immersed in a 1 wt% aqueous sodium hydroxide solution and then a 1 wt% aqueous sulfuric acid solution, and finally the test piece was immersed for 10 minutes in a distilled water mixture containing 1 wt% ethanolamine at 95°C to subject the surface to boehmite treatment, thereby obtaining an aluminum (A1050) plate whose surface had been physically treated and then chemically treated.

[0087] The obtained aluminum (A1050) plate was placed in an injection molding machine mold set to a mold temperature of 150°C, and the obtained polyarylene sulfide resin composition was placed into the hopper of an injection molding machine (manufactured by Sumitomo Heavy Industries, product name: SE75S) heated to 310°C, and injection insert molding was performed to obtain an aluminum member-polyarylene sulfide resin composition member composite measuring 70 mm x 70 mm x 2 mm (thickness) (size ratio in the vertical and horizontal directions relative to the thickness direction of the laminate layer: 35).

[0088] The dielectric constant, dielectric loss tangent, impact resistance, metal bondability, and amount of displacement of the obtained polyarylene sulfide resin composition and the aluminum member-polyarylene sulfide resin composition member composite were evaluated. The evaluation results are shown in Table 1.

[0089] The obtained polyarylene sulfide resin composition and aluminum member-polyarylene sulfide resin composition member composite had good metal bonding properties and warpage, and also exhibited practically sufficient values ​​for dielectric constant, dielectric loss tangent, and impact resistance.

[0090] Example 6 78.3% by weight of PPS (A-3) obtained in Synthesis Example 3, 20% by weight of ethylene copolymer (B-3), and 1.7% by weight of release agent (D-1) were mixed uniformly in advance and fed into the hopper of a twin-screw extruder (Toshiba Machine, (product name) TEM-35-102B) heated to a cylinder temperature of 300°C. On the other hand, glass fiber (C-1) was fed from the hopper of the side feeder of the twin-screw extruder, melt-kneaded, and pelletized to obtain a polyarylene sulfide resin composition. The composition ratio of the polyarylene sulfide resin composition at that time was 47% by weight of PPS (A-3), 12% by weight of ethylene copolymer (B-2), 40% by weight of glass fiber (C-1), and 1% by weight of release agent (D-1).

[0091] On the other hand, an aluminum alloy (A5052) plate (20 mm × 20 mm × 1 mm (thickness)) was immersed in ethanol to clean the surface, and then the test piece was immersed in a distilled water mixture containing 0.5% by weight of ethanolamine at 95°C for 5 minutes to perform a boehmite treatment, thereby obtaining an aluminum alloy (A5052) plate with a chemically treated aluminum alloy surface.

[0092] The obtained aluminum alloy (A5052) plate was placed in an injection molding machine mold with the mold temperature set to 150°C, and the obtained polyarylene sulfide resin composition was placed in the hopper of an injection molding machine (manufactured by Sumitomo Heavy Industries, product name: SE75S) heated to 310°C, and injection insert molding was performed to obtain an aluminum alloy part-polyarylene sulfide resin composition part composite measuring 20 mm x 20 mm x 2 mm (thickness) (the size ratio in the vertical and horizontal directions to the thickness direction of the laminate layer is 10).

[0093] The obtained polyarylene sulfide resin composition and the aluminum alloy member-polyarylene sulfide resin composition member composite were evaluated for dielectric constant, dielectric loss tangent, impact resistance, metal bondability, and amount of displacement. The evaluation results are shown in Table 1.

[0094] The obtained polyarylene sulfide resin composition and aluminum alloy member-polyarylene sulfide resin composition member composite had good metal bonding properties and warpage, and also exhibited practically sufficient values ​​for dielectric constant, dielectric loss tangent, and impact resistance.

[0095] Example 7 86.4% by weight of PPS (A-1) obtained in Synthesis Example 1, 12.7% by weight of ethylene copolymer (B-2), and 0.9% by weight of release agent (D-2) were mixed uniformly in advance and fed into the hopper of a twin-screw extruder (Toshiba Machine, (product name) TEM-35-102B) heated to a cylinder temperature of 300°C. On the other hand, glass fiber (C-1) was fed from the hopper of the side feeder of the twin-screw extruder, melt-kneaded, and pelletized to obtain a polyarylene sulfide resin composition. The composition ratio of the polyarylene sulfide resin composition at that time was 47.5% by weight of PPS (A-1), 7% by weight of ethylene copolymer (B-2), 45% by weight of glass fiber (C-1), and 0.5% by weight of release agent (D-2).

[0096] On the other hand, an aluminum die-cast alloy (ADC12) plate (20 mm × 20 mm × 1 mm (thickness)) was immersed in acetone to clean the surface, and then the test piece was subjected to laser treatment in which a laser with a wavelength of 1.064 μm was used to scan the plate 120,000 times in the orthogonal direction with a hatching width of 0.2 mm, a frequency of 6 KHz, and a speed of 100 mm / sec, thereby obtaining an aluminum die-cast alloy (ADC12) plate with a physically treated aluminum die-cast alloy surface.

[0097] The obtained aluminum die-cast alloy (ADC12) plate was placed in an injection molding machine mold with the mold temperature set to 150°C, and the obtained polyarylene sulfide resin composition was poured into the hopper of an injection molding machine (manufactured by Sumitomo Heavy Industries, product name: SE75S) heated to 310°C, and injection insert molding was performed to obtain an aluminum die-cast alloy part-polyarylene sulfide resin composition part composite measuring 20 mm x 20 mm x 2 mm (thickness) (the ratio of the size in the vertical and horizontal directions to the thickness direction of the laminate layer was 10).

[0098] The dielectric constant, dielectric loss tangent, impact resistance, metal bondability, and amount of displacement of the obtained polyarylene sulfide resin composition and the aluminum die-cast alloy member-polyarylene sulfide resin composition member composite were evaluated. The evaluation results are shown in Table 1.

[0099] The obtained polyarylene sulfide resin composition and the aluminum die-cast alloy member-polyarylene sulfide resin composition member composite had good metal bonding properties and warpage, and also showed practically sufficient values ​​for dielectric constant, dielectric loss tangent, and impact resistance.

[0100] [Table 1]

[0101] Comparative Examples 1 to 6 PPS (A-1), ethylene copolymer (B-1), and release agent (D-1) were mixed in the composition ratio shown in Table 2 and fed into the hopper of a twin-screw extruder, and glass fibers (C-1 to C-3) were fed into the hopper of a side feeder of the twin-screw extruder so as to obtain the composition ratio shown in Table 2. A resin composition was obtained in the same manner as in Example 1.

[0102] On the other hand, by the same method as in Example 1, an aluminum alloy (A5052) plate was obtained whose surface was chemically treated.

[0103] An aluminum alloy member-resin composition member laminate was obtained in the same manner as in Example 1, except for using the obtained resin composition.

[0104] The obtained resin composition and the aluminum alloy member-resin composition member laminate were evaluated for dielectric constant, dielectric tangent, impact resistance, metal bondability, and amount of displacement. The evaluation results are shown in Table 2.

[0105] The resin composition obtained in Comparative Example 1 was inferior in dielectric constant and dielectric dissipation factor. The resin composition obtained in Comparative Example 2 was inferior in dielectric constant and dielectric dissipation factor. The resin composition obtained in Comparative Example 3 was inferior in the amount of warping. The resin composition obtained in Comparative Example 4 was inferior in dielectric constant and dielectric dissipation factor. The resin composition obtained in Comparative Example 5 was inferior in the amount of warping. The resin composition obtained in Comparative Example 6 was inferior in metal bonding property and impact resistance.

[0106] [Table 2] [Industrial Applicability]

[0107] INDUSTRIAL APPLICABILITY The polyarylene sulfide resin composition of the present invention has a low dielectric constant and a low dielectric loss tangent, and therefore has excellent radio wave transmittance in the megahertz to gigahertz range, exhibits little warping when integrated with a metal member, has good bonding properties with the metal member, and is also excellent in impact resistance. It is expected that the polyarylene sulfide resin composition of the present invention will be used as a resin composition or a composite comprising the same for electronic / electrical component applications such as housings for mobile terminal devices such as mobile PCs, tablets, and mobile phones that use radio waves in the megahertz to gigahertz range for communication, or for electrical component applications such as automotive electrical components.

Claims

1. A polyarylene sulfide resin composition comprising 39.3 to 51.5% by weight of polyarylene sulfide (A), 4.0 to 10.0% by weight of an ethylene polymer (B) which is at least one modified ethylene polymer selected from the group consisting of ethylene-α,β-unsaturated carboxylic acid alkyl ester-maleic anhydride copolymer, ethylene-α,β-unsaturated carboxylic acid glycidyl ester-vinyl acetate copolymer, ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid alkyl ester copolymer, and maleic anhydride graft-modified ethylene polymer, and 40.0 to 55.0% by weight of glass fiber (C) having a dielectric constant of 5.5 or less at 2 GHz and a fiber cross-sectional aspect ratio of 2 to 4, wherein the polyarylene sulfide resin composition has a dielectric constant of 3.5 or less and a dielectric dissipation factor of 0.010 or less as measured at a measurement frequency of 2 GHz in accordance with JIS C-2565, and the polyarylene sulfide (A) is an amino group-modified polyarylene sulfide.

2. The polyarylene sulfide resin composition according to claim 1, further comprising at least one release agent (D) selected from the group consisting of polyethylene wax, polypropylene wax, carnauba wax, and fatty acid amide wax.

3. The polyarylene sulfide resin composition according to claim 1 or 2, characterized in that the polyarylene sulfide (A) is a polyarylene sulfide having a melt viscosity of 100 to 700 poise when measured under conditions of a temperature of 315°C and a load of 10 kg using a high-temperature flow tester equipped with a die having a diameter of 1 mm and a length of 2 mm.

4. A metal member having a surface which has been subjected to a physical and / or chemical treatment, 39.3 to 51.5% by weight of polyarylene sulfide (A), 4.0 to 10.0% by weight of an ethylene polymer (B) which is at least one modified ethylene polymer selected from the group consisting of ethylene-α,β-unsaturated carboxylic acid alkyl ester-maleic anhydride copolymer, ethylene-α,β-unsaturated carboxylic acid glycidyl ester-vinyl acetate copolymer, ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid alkyl ester copolymer, and maleic anhydride graft-modified ethylene polymer, and 40.0 to 55.0% by weight of glass fiber (C) having a dielectric constant of 5.5 or less at 2 GHz and a fiber cross-sectional aspect ratio of 2 to 4, wherein the ethylene polymer (B) is a glass fiber having a dielectric constant of 5.5 or less at 2 GHz and a fiber cross-sectional aspect ratio of 2 to 4, and A metal member-polyarylene sulfide resin composition member composite is characterized in that the metal member-polyarylene sulfide resin composition member composite has a dielectric constant of 3.5 or less and a dielectric dissipation factor of 0.010 or less, as measured at a measurement frequency of 2 GHz in accordance with C-2565, and is a direct integration product of an injection-molded member and a polyarylene sulfide resin composition in which the polyarylene sulfide (A) is an amino group-modified polyarylene sulfide.

5. A metal member-polyarylene sulfide resin composition member composite as described in claim 4, characterized in that it includes a laminate having a thickness of 0.5 to 5 mm and having a ratio of length and width to thickness of 10 or more.

Citation Information

Patent Citations

  • Character generator

    JP1988052186A

  • Polyphenylene sulfide resin composition and its molded article

    JP2002129014A

  • Insert molded product

    JP2005161693A

  • Polyphenylene sulfide resin composition and molded article

    JP2005306926A

  • Polyarylene sulfide resin composition and injection molding

    JP2006328291A